Sexual orientation, disclosure and earnings - Erik Plug; Peter Berkhout (Institute for the Study of Labor (IZA), 2008)
Gay/bisexual workers tend to earn less than other men. Does this occur because of discrimination or because of selection? In this paper we address this question and collect new information on workplace disclosure to separate out discrimination effects from selection effects. Using a large sample of recently graduated men in the Netherlands, we find that gay/bisexual workers earn about 3 to 4 percent less than other men. Our disclosure estimates, however, provide little evidence that the labor market discriminates against gay/bisexual workers. They rather support the selection story, most prominently observed among undisclosed gay/bisexual workers who concentrate in lower paid occupations, and earn about 5 to 9 percent less than other men.
Keywords: J15; 330; Sexual orientation; disclosure; earnings; discrimination; selection; Lohndifferenzierung; Sexualität; Homosexualität; Arbeitsmarktdiskriminierung; Auskunftspflicht; Niederlande